2004
DOI: 10.1143/jjap.43.l180
|View full text |Cite
|
Sign up to set email alerts
|

Improved External Efficiency InGaN-Based Light-Emitting Diodes with Transparent Conductive Ga-Doped ZnO as p-Electrodes

Abstract: Transparent conductive Ga-doped ZnO (ZnO:Ga) was fabricated to serve as p-contacts of InGaN-based light-emitting diodes (LEDs) using molecular-beam epitaxy. As-grown ZnO:Ga films typically have resistivities of ¼ 2 À 4 Â 10 À4 Ácm, and over 80% transparency in the near UV and visible wavelength ranges. The current-voltage characteristics between as-grown ZnO:Ga contacts and p-GaN layers were ohmic. The brightness of LEDs fabricated with ZnO:Ga p-contacts was nearly double compared to LEDs with conventional Ni/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…[50][51][52][53][54] However, TCO-based TCEs with desired electrical resistance have fairly low transmittances in the UV spectrum. Thus, to enhance both the UV transmittance and the electrical properties of TCEs, various approaches, including metal-doped TCOs, [55][56][57][58][59][60] oxide/metal/oxide structure, 61 and surface treatments, 62,63 have been investigated. Metal-doped TCOs, such as Sb-doped tin oxide (ATO), 56 Gadoped ZnO (GZO), 59 Al-doped ZnO (AZO), 60 and Ti-, Al-, Ga-, and Ge-doped ITO, 57,58 have been investigated as a candidate for near UV (NUV) p-type TCEs because of their reasonable electrical resistance and high optical transmittance in the NUV spectrum.…”
Section: Ohmic Contacts To P-gan For Near Uv Ledsmentioning
confidence: 99%
“…[50][51][52][53][54] However, TCO-based TCEs with desired electrical resistance have fairly low transmittances in the UV spectrum. Thus, to enhance both the UV transmittance and the electrical properties of TCEs, various approaches, including metal-doped TCOs, [55][56][57][58][59][60] oxide/metal/oxide structure, 61 and surface treatments, 62,63 have been investigated. Metal-doped TCOs, such as Sb-doped tin oxide (ATO), 56 Gadoped ZnO (GZO), 59 Al-doped ZnO (AZO), 60 and Ti-, Al-, Ga-, and Ge-doped ITO, 57,58 have been investigated as a candidate for near UV (NUV) p-type TCEs because of their reasonable electrical resistance and high optical transmittance in the NUV spectrum.…”
Section: Ohmic Contacts To P-gan For Near Uv Ledsmentioning
confidence: 99%
“…The uses of ZnO-based materials as alternative TCOs are expanding to flat panel displays [1], light emitting diodes [2] and solar cells [3]. High crystalline quality is not always a requirement for TCO applications, but the need for compatibility with established fabrication processes should be emphasized.…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, it has been reported that a Ga-doped ZnO transparent conductive oxide layer contacting to p-GaN results in a twofold higher brightness in GaN UV LEDs, in comparison to the conventional Ni/Au p-contacts. 5 Semiconductor nanowires have attracted extensive attention due to their dramatically enhanced electron-hole interaction from a reduced dimensionality. ZnO one-dimensional (1-D) nanostructures have been grown on various substrates including Si, glass, and c-sapphire at low temperature (~400°C) by metalorganic chemical vapor deposition (MOCVD) via a catalyst-free self-nucleation growth.…”
Section: Introductionmentioning
confidence: 99%